2019
DOI: 10.1158/1078-0432.ccr-18-0277
|View full text |Cite
|
Sign up to set email alerts
|

The Ewing Family of Tumors Relies on BCL-2 and BCL-XL to Escape PARP Inhibitor Toxicity

Abstract: Purpose: It was recently demonstrated that the EWSR1-FLI1 t(11;22)(q24;12) translocation contributes to the hypersensitivity of Ewing sarcoma to PARP inhibitors, prompting clinical evaluation of olaparib in a cohort of heavily pretreated Ewing sarcoma tumors. Unfortunately, olaparib activity was disappointing, suggesting an underappreciated resistance mechanism to PARP inhibition in patients with Ewing sarcoma. We sought to elucidate the resistance factors to PARP inhibitor therapy in Ewing sarcoma and identif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 67 publications
(81 reference statements)
0
21
0
1
Order By: Relevance
“…On the other hand, microsatellite instability (MSI) is closely related to DNA MMR deficiency (dMMR). To date, MSI has been identified to affect cancer response to chemotherapies and could regulate PD-1 blockade response in the solid tumor 29,30. Gryfe et al reported that dMMR tumors had significantly more favorable prognosis,31 and this result was supported by other researchers 32.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…On the other hand, microsatellite instability (MSI) is closely related to DNA MMR deficiency (dMMR). To date, MSI has been identified to affect cancer response to chemotherapies and could regulate PD-1 blockade response in the solid tumor 29,30. Gryfe et al reported that dMMR tumors had significantly more favorable prognosis,31 and this result was supported by other researchers 32.…”
Section: Discussionmentioning
confidence: 74%
“…EWSR/FLI1 protein regulates multiple target gene expression, which acts as a critical in ES. Heisey et al found that EWSR/FLI1 fusion would increase BCL-2 expression, and thereby induce drug resistant to PARP inhibitors, and BCL-2 and BCL-XL inhibition could significantly reverse the drug resistance in ES. 30 FOXO1 is a cancer suppressor in multiple cancer types,4547 which significantly inhibited cell proliferation and clone formation ability in ES cell 48.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them have been stated involved in the tumorigenesis and progression of ES. A previous study revealed that BCL2 interacted with BCLXL to escape PARP inhibitor toxicity in ES [33]. The density of CD68-positive Tumor-associated macrophages was found in ES tissue samples and statistically correlated with clinical parameters [34].…”
Section: Discussionmentioning
confidence: 83%
“…During this project, it was reported that resistance to the PARPi olaparib in ES cell lines could be overcome with the pan-BCL2 inhibitor navitoclax [41]. Motivated by that work and by our own findings, we screened small molecules inhibitors that were selective for individual BCL2 family members: venetoclax (BCL2), S63845 (MCL), and A-1331852 (BCL-XL).…”
Section: Resultsmentioning
confidence: 99%